Immune Responses Induced in Chickens by Capsular Extract of P. Multocida Isolated From Farm Rat - Akter, Mashuda; Hossain, Md Mosaraf; Hassan, Md Kamrul; Yadav, Ravi; Morsheda, Fahima; Khan, Md Shahidur Rahman; Siddique, Mahbubul Pratik (Research in Agriculture Livestock and Fisheries, 2021)
An experiment was conducted to investigate the immune response induced in chickens by capsular extract of Pasteurella multocida isolated from rats wandering in and around the poultry farms. The rat isolate of P. multocida was isolated and identified by cultural, morphological, and biochemical characteristics, followed by capsular extract preparation and experimental vaccine development. The isolated P. multocida was found Gram-negative, non-motile, non-spore forming rod occurring singly or pains and occasionally as chains or filaments in Gram’s-staining method. The isolates consistently produced acid from dextrose, sucrose and mannitol but not fermented maltose or lactose. The Capsular antigen was extracted and confirmed by acriflavine test. Finally, experimental fowl cholera vaccine was prepared. Primary vaccination was performed at the dose rate of 5.6×107 CFU/ml through intramuscular and subcutaneous routes in birds of group A (10 birds) and group B (10 birds) and group C (10 birds) were control birds. Secondary vaccination was similarly performed after 15 days of primary vaccination in groups A and B. The levels of pre-vaccination and post-vaccination sera were determined by passive haemagglutination test. The passive haemagglutination antibody titre was recorded on 15 and 35 days of post vaccination in groups A and B. It was demonstrated that experimental capsular extract fowl cholera vaccine conferred 100% protection (p<0.01) against challenge infection and found to be safe. It could be suggested that after thorough field trial, the experimentally prepared capsular extract FC vaccine using rat isolate of P. multocida may be used side by side with conventional FC vaccine. Res. Agric., Livest. Fish.8(1): 117-124, April 2021